The Effectiveness of Non-Pharmacological Therapy "Thought Stopping” of Dysmenorrhea In Students at The Hermina Health Institute - Hartati, Suryani; Laela, Sri (Nusantara Science and Technology Proceedings, 2024)
Students or Adolescent girls usually experience dysmenorrhea, which can interfere with their daily activities. This can be overcome by using non-pharmacological therapy: thought stopping. This study aimed to determine how Thought Stopping therapy impacts dysmenorrhea in students at Hermina Health Institute. This research was conducted through a quasi-experiment with a pre-test design and post-test design with the control group. This research involved 48 respondents and was conducted from January to April 2024. This study used a questionnaire about dysmenorrhea pain and the Numeric Pain Scale (NPS) pain scale. The research results showed that 52% of students aged 18-21 years always experienced dysmenorrhea. They experienced a decrease in pain level from moderate (scale 4) to mild (scale 2) after non-pharmacological therapy: Thought stopping distraction therapy was carried out, with a p-value of 0.038, before and after non-pharmacological therapy: Thought stopping. Nurse's nursing action is non-pharmacological therapy: thought stopping can reduce the level of pain in students Hermina Health Institute as a result of dysmenorrhea. In addition, there was a significant difference between the level of change in pain before and after the procedure. It is hoped that students at Hermina Health Institute can apply non-pharmacological therapy: thought stopping to reduce dysmenorrhea.